1998
DOI: 10.1039/a805109g
|View full text |Cite
|
Sign up to set email alerts
|

Utility of isolated hepatocytes and radio-HPLC-MSn for the analysis of the metabolic fate of 19-nortestosterone laurate in cattle†

Abstract: The metabolic fate of 19-nortestosterone laurate in cattle was investigated to evaluate target analyte(s) appropriate to surveillance for illicit use as a growth promoting agent. Bovine hepatocytes were incubated with either [3H]19-nortestosterone laurate (19-NTL; 4-estren-17 beta-laurate-3-one) or [3H]19-nortestosterone (19-NT; 4-estren-17 beta-ol-3-one; nandrolone). Hepatocyte medium was extracted with solid phase C18 media and analysed by narrow bore radio-HPLC-MSn (LCQ, Finnigan) to evaluate the structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In the present preliminary application of LC-MS, attempts to identify the major bile and urine metabolites were hindered by poor molecular ion formation produced by the estranes, which was possibly exacerbated by interference from matrix co-extractives. Some of the problems encountered have been addressed in parallel studies using hepatocytes to investigate biotransformation by the liver in steers; 19 these studies used positive ion LC-APCI-MS 2 and comparison with reference standards indicated biotransformation to 4-estren-17a-ol-3-one, 4-estrene-3,17-dione (major metabolite after 1 h), n-hydroxy-4-estrene-3,17-dione, n-hydroxy-4-estren-17-ol-3-one, 5b-estran-3a-ol-17-one and 5b-estrane-3a,17b-diol (major metabolite after 4 h of incubation) and (by ESI-MS 2 ) their respective glucuronide conjugates.…”
Section: Urine and Bile Metabolite Profilesmentioning
confidence: 99%
“…In the present preliminary application of LC-MS, attempts to identify the major bile and urine metabolites were hindered by poor molecular ion formation produced by the estranes, which was possibly exacerbated by interference from matrix co-extractives. Some of the problems encountered have been addressed in parallel studies using hepatocytes to investigate biotransformation by the liver in steers; 19 these studies used positive ion LC-APCI-MS 2 and comparison with reference standards indicated biotransformation to 4-estren-17a-ol-3-one, 4-estrene-3,17-dione (major metabolite after 1 h), n-hydroxy-4-estrene-3,17-dione, n-hydroxy-4-estren-17-ol-3-one, 5b-estran-3a-ol-17-one and 5b-estrane-3a,17b-diol (major metabolite after 4 h of incubation) and (by ESI-MS 2 ) their respective glucuronide conjugates.…”
Section: Urine and Bile Metabolite Profilesmentioning
confidence: 99%
“…GC/MS was used as a detection method, with a LOD of 0.02 ng/ml [28]. Structural modifications of nortestosterone, such as esterification of the 17␤-position, allow the compound to be administered via intramuscular injection [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%